Pengembangan Multimedia berbasis Libreoffice Impress pada Tema Prasasti – Prasasti Sriwijaya - wahyuni, fadela septi; Safitri, Sani; Hudaidah, Hudaidah (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2020)
This research entitled "Development Based Multimedia LibreOffice Impress On the Subject of History in Class X at Senior High School number 4 Palembang" contains data on the Role of Inscription-inscription Sriwijaya In Explaining Political Life, Social Religious, and Economic kingdom of Srivijaya, this research has been carried out and implemented in the classroom X Science 1 at Senior High School number 4 Palembang. This research is the development of research development model Hanafin Peck. As for the formulation of the problem in this research is how to develop Based Multimedia Libreoffice Impress On the Subject of History in Class X at Senior High School number 4 Palembang valid, and how to develop Multimedia Based Libreoffice Impress On the Subject of History in Class X at Senior High School number 4 Palembang has an impact effectiveness. Furthermore, the purpose of this research is to develop a valid instructional media and have an impact effectiveness. Influence Based Multimedia LibreOffice Impress Impress On History Lesson in Class X at Senior High School number 4 Palembang visible on improving learning outcomes of students before and after using instructional media at the stage of field trials of 36.57% with Ngain of 0.7. This indicates Based Multimedia LibreOffice Impress Impress a valid value and effectiveness.